2007
DOI: 10.1111/j.1472-765x.2007.02286.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of culture, ELISA and PCR assays for the detection of Salmonella in seafood

Abstract: Aims:  The study evaluated the efficiency of culture, enzyme‐linked immunosorbent assay (ELISA) and polymerase chain reaction (PCR) assays for the detection of Salmonella in naturally contaminated seafood. Methods and Results:  In this study, 215 seafood samples comprising fish, shrimp, crab, clam, mussel, oyster, squid, cuttlefish and octopus from fish market of Cochin (India), were compared by culture, ELISA and PCR methods. Bacteriological Analytical Manual (BAM), U.S. Food and Drug Administration (USFDA) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 19 publications
1
49
3
Order By: Relevance
“…was isolated [21] . Contrary to this, the studies which had higher results (90.0%, 43.8% and 30.5%) than ours were reported by Jegadeeshkumar et al [22] , Budiati et al [23] and Kumar et al [6] respectively. The reason for high contamination rate should be due to the use of contaminated raw materials, detection methods and the geographical conditions.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…was isolated [21] . Contrary to this, the studies which had higher results (90.0%, 43.8% and 30.5%) than ours were reported by Jegadeeshkumar et al [22] , Budiati et al [23] and Kumar et al [6] respectively. The reason for high contamination rate should be due to the use of contaminated raw materials, detection methods and the geographical conditions.…”
Section: Discussioncontrasting
confidence: 53%
“…The prevalence of Salmonella spp. in shrimp samples tested in this study was lower in comparison to those detected by Kumar et al [6] (29.0%), Kumar et al [24] (26.7%) and Hatha & Lakshmanaperumalsamy [20] (%15.2). On the other hand, Koonse et al [25] reported the prevalence rate of Salmonella spp.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The specificity of these phages is partly mediated by tail-associated proteins that distinctively recognize surface molecules of susceptible bacteria (Kretzer et al, 2007). Bacteriophages or proteins of bacteriophages have been included in various ways in detection methods for pathogens (Favrin et al, 2003) Although there is a need to perform a collaborative study to further evaluate the methods before it can be concluded that their performances are equal, both the PCR and the ELFAbased assay could provide a rapid and user-friendly screening method for detection of Salmonella in food (Uyttendaele et al, 2003;Priego et al, 2009;Kumar et al, 2008;Szabo et al, 2008) …”
Section: Vidasmentioning
confidence: 99%